Criminal Law Enforcement Against Violation of Minimum Age of Marriage - Achmad Yustian Jaya Sesunan (Pancasila and Law Review, 2020)
Pancasila as the ideology of the nation which contains values as a philosophy for the life of the nation and state where human values as a form of awareness of human attitudes and actions based on the potential of human conscience in relation to norms and culture in general, it can generally be said that humans free to do whatever he wants, one of which is to do marriage. However, marriage in early childhood has caused several factors including, losing the rights that he should have gotten since childhood. There are a lot of reports about child marriage in Indonesia and conflicting rules between the two Laws (Law), namely Law No. 23 of 2002 concerning Child Protection and Law No. 1 of 1974 concerning Marriage, this is the reason the author examines child marriage from two corners of the Act. In general, law enforcement of violations of the minimum marriage age from the formulation stage has been problematic where the Child Protection Act does not include the Marriage Law in the consideration given, the application stage how it can run optimally if the formulation stage is already problematic, as well as the execution stage how it can provide benefits if there are multiple interpretations. In the enforcement and implementation of child marriage rules even though the Child Protection Act cannot be obstructed even though it has been married according to the Marriage Law. The most fundamental obstacle to law enforcement lies in the inadequacy or incompleteness of the laws and regulations, so that there are many so-called "multiple interpretations" and finally there are doubts in law enforcement. Conditions like this will eventually eventually bring up what is known as "retroactive law" which is certainly full of speculation, and this is very dangerous for the rule of law. The Marriage Law and the Child Protection Act must be revised and the two Laws equalize the rules, especially regarding child marriage rules. This revision needs to be done so as not to confuse and provide legal certainty related to child marriage. It is necessary to include the Marriage Law in the "Remembering" consideration in the Child Protection Act. Both laws must include rules regarding child marriage regulated in the Child Protection Act article so that these two laws harmonize with each other so that they do not cause multiple interpretations. The study was conducted with a type of normative juridical approach and empirical juridical conducted by examining the theories, concepts and legislation related to this research also by looking at the facts and interviews with respondents to gather opinions about law enforcement and factors obstruction of law enforcement violations of the minimum age of marriage.